PROMOTING AT-HOME DISEASE MANAGEMENT OF IBD WITH A MULTIDISCIPLINARY DIGITAL THERAPY APP: SHORT-TERM RESULTS. (22nd January 2022) - Pater, Roeland; Zentveld, Dandyano; Booth, Lisa
Abstract: BACKGROUND: Although current concepts of disease management of Crohn's Disease and ulcerative colitis (IBD) provide evidence of active engagement of patients, such a strategy is difficult to comply with unless multidisciplinary therapy is practiced. In the past years mobile and/or digital health solutions have proven to be competent tools to promote and retain self management for patients across many disease areas. The Nori Health mobile application was developed as multi-faceted digital therapy for IBD based on existing evidence in at-home management and treatment with the aim to accommodate multidisciplinary therapy remotely. OBJECTIVE: The objective of this paper was to report on the retrospective short-term results of a multidisciplinary digital therapy app for the treatment and self-management of IBD; Nori Health. METHODS: Nori Health is a mobile application that digitalizes multidisciplinary therapy, such as education, behavioral intervention and cognitive behavioral therapy (CBT), and is in the market as a CE class I medical device. For the current study, the internal data of anonymized Nori Health users was retrospectively analyzed. User data was evaluated for 8 weeks regarding duration of use (Figures 1, 2) and effect on in-app user reported disease management levels, using the short IBD Control questionnaire (IBD-CONTROL). RESULTS: Data of 273 users were available, of which 29 users completed the IBD-CONTROL questionnaire both prior and after the duration of the analysis period. The gender of the users was 61% female and 39% male. Disease management levels increased 34% from baseline 50 to 67 for all users at the end of the observation period. CONCLUSION: This retrospective study showed that in a randomized population of app users, an app digitalizing multidisciplinary interventions for the self-management of IBD improved user-reported disease management levels significantly. Additional RCTs will be needed to adjust for selection effects, potential bias, and to further improve clinical relevance of these short-term results.